Trekking the Amazon with Love and Care - Eglee Zent; Stanford Zent; Lojta Jtute; Awelajlu Jtitekyo; Jkatalila̧ Jtute; Lobįko Ijtö; Ilę Jkwayo; Maliela Yaluja; Iva Juae; Noe Jono; Alejadro Molö; Aula Amikoja; et al. (Ethnobiology Letters, 2022)
This essay highlights the philosophical views of the Jotï, an Indigenous group from the Venezuelan Amazon. Daily Jotï behaviors are embraced by a notion of life in which everything is interconnected (mana jtïdemame) and should be respected given its sacredness (jkïmañe). Furthermore, life is in perennial movement (jkeibïae dekae) and is designed to be carried out together in groups (uliyena majadïka). The maintenance of life is related to engaging in solidarity, reciprocity, and amicability (me madöna), with these values being the key metaphor for hunting-gathering-farming-fishing rather than predation. The universe is populated by a myriad of entities with unique capacities, volitions, and motivations (budëkïmade)—like those of people, regardless of their nonhuman appearances—evidence that the universe’s inherent condition is subjective, and all life forms originated from the same root. Likewise, no landscape or life form is pristine or final; instead, everything is potentially subject to ceaseless transformation (jka ojtali ~ jkabaemade). Those reasons provide the basis for why every person should strive for righteousness (nï jti maudöna), endeavoring to be morally good and practicing love-care with all that surrounds us (jkyo jkwainï). Love-care is the translation of a praxis considered an innate essential constituent of all persons. It is also the fundamental strategy to sustain and protect life. Given that nothing prevents a person anywhere in the world from embracing love and care as their life motto while struggling to prevent the current path of destruction of the Earth, the enactment of love-care is an endless possibility regardless of location or time.